Evaluation and comparison of a lean production system by using SAE J4000 standard: a case study on the automotive industry in the state of Mexico - Tabares, Lina María; Robles-Cárdenas, Manuel; Pino Romainville, Francisco (Brazilian Journal of Operations & Production Management, 2017)
Lean manufacturing (LM) is a management system focused on eliminating waste and activities that do not add value, with the aim of reducing costs and improving the quality and productivity of organizations. LM has been adopted in diverse industries and several countries due to its advantages in cost, flexibility and rapid response (Muslimen et al., 2013). The objective of this investigation is to analyze the implementation level to the Lean System via the SAE J4000 (SAE 1999a) standard carried out among companies of the State of Mexico automotive industry. In addition, this investigation shows the inferential and descriptive statistics data analysis of Mexican companies compared to the automotive industries in Spain and Brazil. Results show that the implementation level of the automotive industry is at 48.4% in the State of Mexico according to the SAE J4000 standard. Moreover, the involvement of suppliers and the use of lean tools in processes are higher in the State of Mexico compared to automotive industries in Spain and Brazil. However, previous studies ranked the State of Mexico at a lower level of LM in contrast with Spain and Brazil production lines.